Malleability and Pliability of Silk‐Derived Electrodes for Efficient Deformable Perovskite Solar Cells. Issue 8 (27th January 2020) - Ma, Peipei; Lou, Yanhui; Cong, Shan; Lu, Zheng; Zhu, Kaiping; Zhao, Jie; Zou, Guifu
Abstract: For the fabrication of deformable electronic devices, electrodes that are robust against repeated bending, twisting, stretching, folding, reversible plasticizing, and that maintain electrical conductivity, and so on, are required. Malleable and pliable silk‐derived electrodes are fabricated to enable the shape deformation of perovskite solar cells. Moisture‐driven silk‐derived electrodes show reversible plasticization with malleability and pliability, realizing diverse deformation from simple operations (including bending, folding, stretching, etc.) to complicated structures (including flower, bowknot, and paper crane). It is worth noting that the silk‐derived electrodes maintain electrical conductivity (15.8 Ω sq −1 ) compared to their initial value (15 Ω sq −1 ) even after suffering from reversible mechanical plasticization of complicated structures. Deformable perovskite solar cells are fabricated with the silk‐derived electrodes and achieve a power conversion efficiency of 10.40%. The devices maintain 92% of the initial efficiency after 1000 bends at a curvature radius of 2.5 mm. The power does not decline at 50% strain and keeps more than 60% of the initial value after stretching for 50 cycles. Malleability and pliability of silk‐derived electrodes benefit the realization of stretchable perovskite solar cells and deformable electronic devices. Abstract : Malleable and pliable silk‐derived electrodes are fabricated for use in deformable perovskite solar cells with a power conversion efficiency of 10.40%. The devices maintain 92% of initial efficiency after 1000 bends and more than 60% of the initial power after stretching at 50% strain for 50 cycles.